Pencegahan Primer Kekerasan Seksual Anak Melalui Intervensi Berbasis Keluarga di Kota Pontianak - Linda Suwarni; Selviana Selviana; Vidyastuti Vidyastuti (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Sexual violence against children is a global phenomenon in various countries, including Indonesia. The lack of knowledge, attitudes, and self-efficacy of parents in education to prevent sexual violence in children is an obstacle in the primary prevention program for this incident. The purpose of this study was to determine the effectiveness of family-based interventions through Information and Education Communication (IEC) to prevent sexual violence in children on the knowledge, attitudes, and self-efficacy of parents. This research is a quasi-experimental research with a one-group pretest-posttest design. The sample size was 40 parents who have adolescence with a purposive sampling technique. Data were analyzed by paired t-test. The results of this study indicate that family-based intervention effectively increases parents' knowledge, attitudes and self-efficacy s in delivering education to prevent sexual violence in children (p value <0.05). Family-based intention as effective primary prevention of sexual violence against children.